Barriers and Facilitating Factors of Communication in Iranian Educational Health Care Centers: A Systematic Review - Ali Ahmadi; Fatemeh Zeynab Kiani (Kerman University of Medical Sciences, 2019)
Context Communication, as an essential human skill, is one of the most influential factors in the performance of healthcare workers. In fact, the establishment of effective communication with the recipients of healthcare services and patients can increase their satisfaction and quality of life. Due to the paucity of comprehensive research in this area, the present study aimed to investigate the barriers and facilitating factors concerning communication among healthcare workers. Evidence Acquisition This systematic review was conducted by searching PubMed, Scopus, Web of Science, MagIran, Iranmedex, Google Scholar, and SID databases, using the following keywords: "communication", "communication barrier", "communication facilitator", "health system", "nurse", "physician", "faculty member", "teacher", "student", "health manager", and "patient". All searches were conducted within a 10-year period from 2008 to 2018. Results According to our literature review, 44 articles (38 quantitative and 6 qualitative) met the inclusion criteria. In these studies, "pleasant greetings" and "tidy appearance" were the most important factors facilitating the patient-physician relationship, "teacher's modesty", "patience", and "respect for students" were the main factors facilitating the teacher-student relationship, and finally, "responsibility", "empathy", and "companionship" were identified as the most significant factors in the patient-health care worker relationship. On the other hand, the most important barriers to communication in the clinical setting were "poor introduction of the healthcare provider to patients", "high workload and fatigue", and "lack of training on the principles of communication skills and environmental factors". Conclusions Based on the findings, identifying the facilitating factors and barriers to communication is the most important step in the management of health services. Communication skills training can have a beneficial effect on the health education programs for the healthcare staff. In addition, it can improve the efficacy of health services.